The advertising creations network : implications to society and organizations - Pazarzi, Nina E. (SPOUDAI Journal of Economics and Business, 2007)
This article investigates television-advertising production in the context of the systemic thinking. Advertising rhetoric is based on shared codes that are used by particular professional networks of the «urban elites». New technologies, new cinematographic techniques, latest fads, reformed postmodern arguments, etc are developed by «lead users» and subsequently are passed along those networks. In this respect, particular innovative practices can gradually become a partof the «advertising creativity networks» knowledge capital. My paper is based on current theoretical and research trends of diverse disciplines such as sociology, business administration, systemic theory and mass media studies. My objective is to affirm that studies on advertising practice, social representations and cultural production can be redefined in an interdisciplinary sphere by the systemic theory and the social networks theory support.